Sex-dependent GOAL screening performance in adults at risk for obstructive sleep apnea - R.L.M. Duarte; F.J. Magalhães-da-Silveira; D. Gozal (Pulmonology)
Objective To evaluate possible sex-related differences in the performance of the GOAL, a 4-item obstructive sleep apnea (OSA) screening instrument in adults.Methods Between July 2019 and June 2021, this cross-sectional study included consecutively recruited patients from one Brazilian sleep laboratory undergoing overnight polysomnography. Individuals with GOAL scores ≥ 2 of a maximum of 4 points are classified at high risk for OSA diagnosis. Actual OSA severity was based on the apnea-hypopnea index: ≥ 5.0/h as any OSA, ≥ 15.0/h as moderate-to-severe OSA, and ≥ 30.0/h as severe OSA. Performance of the GOAL instrument in women and men was assessed by the discriminatory ability (obtained from area under the curve [AUC]-Receiver Operating Characteristic curves) and 2×2 contingency tables.Results A total of 2,978 subjects (55.3% males) were evaluated. The frequency of GOAL-defined OSA high-risk was statistically higher in men when compared to women (p < 0.001). The GOAL predictive parameters for screening all severity OSA levels were as follows: in females, sensitivity ranging from 58.2% to 78.3% and specificity ranging from 60.0% to 77.6%, while in males, sensitivity ranging from 90.5% to 96.9% and specificity from 20.7% to 46.8%. The GOAL questionnaire had similar discriminatory properties, assessed by AUC, in women and in men: i) any OSA: 0.741 vs. 0.771 (p = 0.204), ii) moderate-to-severe OSA: 0.727 vs. 0.737 (p = 0.595), and iii) severe OSA: 0.728 vs. 0.703 (p = 0.240); respectively.Conclusions The GOAL instrument emerges as a useful tool for screening adult individuals and displays similar performance in both women and men.